Transforming Governance in Indonesia: Exploring New Frontiers in Public Sector Management - Femi Asteriniah; Deby Chintia Hestiriniah (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Indonesia's recent governmental reforms, focusing on the need for enhanced public sector management to cope with modern administrative demands and societal expectations. The primary objective of the research is to evaluate the effectiveness of these reforms and to identify areas for further improvement in Indonesian governance. The methodology employed in this study includes a comprehensive review of existing literature, qualitative analysis of policy documents, and interviews with key stakeholders in the Indonesian government. This multi-faceted approach allows for a thorough understanding of the complexities involved in public sector management reform. The findings reveal significant advancements in transparency, accountability, and public engagement within Indonesia's governance structures. However, challenges such as bureaucratic inertia, inadequate resource allocation, and resistance to change remain prevalent. The study concludes with recommendations for enhancing governance practices, emphasizing the need for continuous innovation and stakeholder engagement in the public sector. This research contributes to the broader discourse on governance reform in developing countries, offering valuable insights for policymakers and practitioners involved in public sector transformation.